Effect and mechanism of Dichloroacetate in the treatment of stroke and the resolution strategy for side effect - Xu Wang; Chunshu Rong; Wei Leng; Ping Niu; Ziqiao He; Gaihua Wang; Xin Qi; Dexi Zhao; Jinhua Li (European Journal of Medical Research, 2025)
Abstract Stroke is a serious disease that leads to high morbidity and mortality, and ischemic stroke accounts for more than 80% of strokes. At present, the only effective drug recombinant tissue plasminogen activator is limited by its indications, and its clinical application rate is not high. Therefore, it is urgent to develop effective new drugs according to the pathological mechanism. In the hypoxic state after ischemic stroke, anaerobic glycolysis has become the main way to provide energy to the brain. This process is essential for the maintenance of important brain functions and has important implications for recovery after stroke. However, acidosis caused by anaerobic glycolysis and lactic acid accumulation is an important pathological process after ischemic stroke. Dichloroacetate (DCA) is an orphan drug that has been used for decades to treat children with genetic mitochondrial diseases. Some studies have confirmed the role of DCA in stroke, but the conclusions are conflicting because some believe that DCA is not effective for ischemic stroke and may aggravate hemorrhagic stroke. This study reviews these studies and finds that DCA has a good effect on ischemic stroke. DCA can protect ischemic stroke by improving oxidative stress, reducing neuroinflammation, inhibiting apoptosis, protecting blood–brain barrier, and regulating metabolism. We also describe the differences in the outcomes of DCA in the treatment of ischemic stroke and the reasons why DCA aggravate hemorrhagic stroke. In addition, DCA, as a water disinfection byproduct, has been concerned about its toxicity. We describe the causes and solutions of peripheral neuropathy caused by DCA. In summary, this study analyzes the neuroprotective mechanism of DCA in ischemic stroke and the contradiction of the different research results, and discusses the causes and solutions of its adverse effects. Graphical Abstract